Community Participation in the Village Fund Program in Kemang Manis Village, Tebing Tinggi District, Empat Lawang Regency, South Sumatra - Adila, Hikmah; Alfatih, Andy; Alfitri (HM Publisher, 2018)
This study aimed to find out how community participation in the Village Fund program in Kemang Manis Village in the Four Lawang District in 2016 and the factors that supported and blocked community participation in the village fund program in Kemang Manis Village. The method used was qualitative so that the data obtained through interviews, observation and study of documentation and qualitative descriptive analysis techniques. The results showed that at the decision making stage, the participation of the Kemang Manis village community in the Village Fund Program in 2016 was still low because the data synchronization activities were not carried out, only the village elite community and workers as well as grant providers, were invited, attended, gave opinions, and approve the results of the meeting's decision. At the implementation stage (community participation) was quite good, it appeared in the crowded community who registered themselves as candidates for village infrastructure activities, following the work briefing and direction from the village government. At the time of implementation the community brought their own carpentry equipment, donated food and drinks, and received wages or daily work incentives, and participants of community empowerment activities received transport money. The stages of the utilization of benefits (benefits) the community felt the benefits of the results of village development. Roads could be passed by 4-wheeled vehicles, making it easier to transport agricultural produce, residents began to build houses because roads were available and land values ​​had also increased. The community had not yet been involved in the monitoring, supervision and evaluation stages, because in the planning stages of the Village RPJM and Village RKP documents the community involvement is still low. At the stage of implementation of village development the community was involved as an implementer, but the procurement and financial management and administration activities were carried out by the village government. There were no complaints from the public and information disclosure regarding the new Village Fund in the form of a Village Infrastructure development project board.